Integrating Technology into Education: Students' Attitudes toward Online Learning - Mahyiddin, Mahyiddin; Amin, Fakhrurrazi M. (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2022)
The increasing spread of the COVID-19 encouraged learning systems to switch from traditional to online learning. It has brought significant problems and difficulties for students. The swift shift to fully online learning demands some adaptation. Students must learn to adapt their abilities because of the increasing use of technology in education. This study explored students' attitudes towards online learning and the reasons for their attitudes. A survey of 191 students from four State Islamic universities in Aceh was conducted online. A descriptive research framework was chosen, and a survey approach was used to collect data to gain knowledge of the situation and answer research questions. Students showed a positive attitude and satisfaction toward online learning during Covid-19. Even they realized how to handle technological tools applied during teaching and learning. Integrating technology into education does not challenge students as technical support and facilitates education to be easier. Keeping up with technology and infrastructural upgrades is vital to support online learning. The recent study has certain limitations. The small number of participants leads to incomplete data. Therefore, it is necessary to include more people to examine education in general.